Risk of gastric or peritoneal recurrence, and long-term outcomes, following pancreatic cancer resection with preoperative endosonographically guided fine needle aspiration - Ngamruengphong, S.; Xu, C.; Woodward, T. A.; Raimondo, M.; Stauffer, J. A.; Asbun, H. J.; Wallace, M. B. (Endoscopy, 2013)
Background and study aims: There have been concerns regarding tumor cell seeding along the needle track or within the peritoneum caused by preoperative endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA). The aim of this study was to evaluate whether preoperative EUS-FNA is associated with increased risk of stomach/peritoneal recurrence and whether the procedure affects long term survival.Methods: The records of patients diagnosed with malignant solid and cystic pancreatic neoplasms who underwent surgery with curative intent between 1996 and 2012 were reviewed.Results: A total of 256 patients with similar baseline characteristics were included: 48 patients in the non-EUS-FNA group and 208 in the EUS-FNA group. Recurrence data were available for 207 patients. Median length of follow-up was 23 months (range 0 – 111 months). A total of 19 patients had gastric or peritoneal recurrence; 6 (15.4 %) in the non-EUS-FNA group vs. 13 (7.7 %) in the EUS-FNA group (P = 0.21). Three patients had recurrence in the stomach wall: one (2.6 %) patient in the non-EUS-FNA group vs. two patients (1.2 %) in EUS-FNA group (P = 0.46). A total of 16 patients had peritoneal recurrence: 5 patients (12.8 %) in the non-EUS-FNA group and 11 patients (6.5 %) in the EUS-FNA group (P = 0.19). In a multivariate analysis, undergoing EUS-FNA was not associated with increased cancer recurrence or decreased overall survival. Conclusion: Pre-operative EUS-FNA was not associated with an increased rate of gastric or peritoneal cancer recurrence in patients with resected pancreatic cancer. Two patients had gastric wall recurrence following the procedure, but this may be explained by direct tumor extension. This suggests that EUS-FNA is not associated with an increased risk of needle track seeding.